Computational thinking for young indigenous learners in New Zealand - Wendy Fox‐Turnbull; Shaoqun Wu; Tiana Mayo; Matthew Stafford; Swati Gulati (Future in Educational Research)
Abstract Computational thinking, a key component for digital technologies, is defined as an approach to problem‐solving, designing computer systems, and understanding related human behaviours, while drawing on fundamental ideas of computing. It is critical that all young students acquire computational thinking skills during their school age. Technology practice is most successful when embedded within authentic contexts, thus this paper presents a study that facilitated the learning of two concepts of computational thinking: sequencing and orientation within culturally embedded technology practice. The study examines what pedagogies most effectively facilitate computational thinking learning for young Māori learners. In particular, what is the role of using authentic contexts in young Māori learners learning computational thinking? and what teaching strategies engage students effectively? The 4‐week study was undertaken at a local Primary School with a high Māori roll in a low socioeconomic area. The findings suggested that the learning is more effective when the concepts of computation thinking were embedded in the students' cultural and local environment (language, places, stories) through the learning context and the pedagogical strategies.